Autophagy Mediates HBx‐Induced Nuclear Factor‐κB Activation and Release of IL‐6, IL‐8, and CXCL2 in Hepatocytes. Issue 10 (October 2015) - Luo, Millore X.M.; Wong, Sunny H.; Chan, Matthew T.V.; Yu, Le; Yu, Sidney S.B.; Wu, Feng; Xiao, Zhangang; Wang, Xiaojuan; Zhang, Lin; Cheng, Alfred S.L.; Ng, Simon S.M.; Chan, Francis K.L.; et al.
<x xml:space="preserve">Abstract</x> Hepatitis B virus (HBV) and one of its encoded proteins, HBV X protein (HBx), have been shown to induce autophagy in hepatoma cells. Substantial evidence indicates that autophagy is a potent suppressor of inflammation. However, sporadic reports suggest that autophagy could promote pro‐inflammatory cytokine expression and inflammation in some biological contexts. Here, we show that overexpression of HBx induces LC3B‐positive autophagosome formation, increases autophagic flux and enhances the expression of ATG5, ATG7, and LC3B‐II in normal hepatocytes. Abrogation of autophagy by small interfering RNA against ATG5 and ATG7 prevents HBx‐induced formation of autophagosomes. Autophagy inhibition also abrogates HBx‐induced activation of nuclear factor‐κB (NF‐κB) and production of interleukin‐6 (IL‐6), IL‐8, and CXCL2. These findings suggest that autophagy is required for HBx‐induced NF‐κB activation and pro‐inflammatory cytokine production and could shed new light on the complex role of autophagy in the modulation of inflammation. J. Cell. Physiol. 230: 2382–2389, 2015. © 2015 Wiley Periodicals, Inc.